2015
DOI: 10.1007/s00300-015-1679-y
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic light requirements and vertical distribution of macroalgae in newly ice-free areas in Potter Cove, South Shetland Islands, Antarctica

Abstract: In Potter Cove, Antarctica, newly ice-free areas appeared due to glacial retreat. Simultaneously, the inflow of sediment increased, reducing underwater photosynthetically active radiation (PAR, 400-700 nm). The aim of this study was to determine the photosynthetic characteristics of two macroalgal species colonizing three newly icefree areas, A1, A2 and A3, with increasing degree of glacial influence from A1 to A3. Turbidity, salinity and temperature were measured, and light attenuation coefficients (K d ) cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
80
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(94 citation statements)
references
References 64 publications
4
80
0
10
Order By: Relevance
“…In the present study, the lower irradiance PAR values assessed in Island D compared to Peñón de Pesca are consistent with previous findings that have shown that the inflow of sediment during the warmer months leads to marked seasonal variations in turbidity (Deregibus et al, 2016). Algal growth is constrained during 2 (two) or 3 (three) months a year until the sediment enters the water column (Wiencke and Amsler, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In the present study, the lower irradiance PAR values assessed in Island D compared to Peñón de Pesca are consistent with previous findings that have shown that the inflow of sediment during the warmer months leads to marked seasonal variations in turbidity (Deregibus et al, 2016). Algal growth is constrained during 2 (two) or 3 (three) months a year until the sediment enters the water column (Wiencke and Amsler, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…An increase in sediment input can also have positive effects in reducing exposure to excessive ultraviolet radiation (280-400 nm), and current circulation and wind cause resuspension processes (Schloss et al, 2012). Seaweeds in Potter Cove are not only shade-adapted but can also cope with high PAR intensities in summer as they are not photoinhibited even under very high irradiances (Deregibus et al, 2016;Wiencke and Amsler, 2012). Quartino et al (2013) reported the presence of both G. skottsbergii and H. grandifolius in areas with high sedimentation showing that survival and reproduction skills of these algae under such circumstances are successful.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations